2020
DOI: 10.1021/acs.jproteome.9b00868
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Examination of the Mouse Lung Metabolome Following Mycobacterium tuberculosis Infection Using a Multiplatform Mass Spectrometry Approach

Abstract: The mechanisms whereby Mycobacterium tuberculosis (Mtb) rewires the host metabolism in vivo are surprisingly unexplored. Here, we used three high-resolution mass spectrometry platforms to track altered lung metabolic changes associated with Mtb infection of mice. The multiplatform data sets were merged using consensus orthogonal partial least squares-discriminant analysis (cOPLS-DA), an algorithm that allows for the joint interpretation of the results from a single multivariate analysis. We show that Mtb infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 125 publications
1
41
0
1
Order By: Relevance
“…Lung metabolome characterization in bacterial infections has been performed in Mycobacterium tuberculosis infection (four studies, two in guinea pigs [12,13] and two in C57BL/6 mice [14,15]), using NMR [12,13,14] and capillary electrophoresis-mass spectrometry (CE-MS), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS) [15]; in Pseudomonas aeruginosa infection (two studies in C57BL/6 mice, one using NMR [16] and one using time-of-flight-secondary ion mass spectrometry (TOF-SIMS)MS [17]); and in Francisella tularensis infection in ICR mice using desorption electrospray ionization-mass spectrometry (DESI-MS) [18]. Given the common methods employed in most of the M. tuberculosis studies, significant overlap in infection-induced metabolic shifts was observed, including increases in lactate, glutamate, aspartate, glutathione, and betaine (Table 1) [12,13,14,15]. Increases in oxidized glutathione are likely due to inflammatory processes [12,15], and increases in amino acids may reflect increased proteolysis [15].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lung metabolome characterization in bacterial infections has been performed in Mycobacterium tuberculosis infection (four studies, two in guinea pigs [12,13] and two in C57BL/6 mice [14,15]), using NMR [12,13,14] and capillary electrophoresis-mass spectrometry (CE-MS), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS) [15]; in Pseudomonas aeruginosa infection (two studies in C57BL/6 mice, one using NMR [16] and one using time-of-flight-secondary ion mass spectrometry (TOF-SIMS)MS [17]); and in Francisella tularensis infection in ICR mice using desorption electrospray ionization-mass spectrometry (DESI-MS) [18]. Given the common methods employed in most of the M. tuberculosis studies, significant overlap in infection-induced metabolic shifts was observed, including increases in lactate, glutamate, aspartate, glutathione, and betaine (Table 1) [12,13,14,15]. Increases in oxidized glutathione are likely due to inflammatory processes [12,15], and increases in amino acids may reflect increased proteolysis [15].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Given the common methods employed in most of the M. tuberculosis studies, significant overlap in infection-induced metabolic shifts was observed, including increases in lactate, glutamate, aspartate, glutathione, and betaine (Table 1) [12,13,14,15]. Increases in oxidized glutathione are likely due to inflammatory processes [12,15], and increases in amino acids may reflect increased proteolysis [15]. Succinate was also increased in P. aeruginosa infection, whereas glutathione was decreased [16].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
See 3 more Smart Citations